Fast-food consumption, diet quality and body weight: cross-sectional and prospective associations in a community sample of working adults. Issue 5 (15th June 2015) - Barnes, Timothy L; French, Simone A; Mitchell, Nathan R; Wolfson, Julian
Abstract: Objective: To examine the association between fast-food consumption, diet quality and body weight in a community sample of working adults. Design: Cross-sectional and prospective analysis of anthropometric, survey and dietary data from adults recruited to participate in a worksite nutrition intervention. Participants self-reported frequency of fast-food consumption per week. Nutrient intakes and diet quality, using the Healthy Eating Index-2010 (HEI-2010), were computed from dietary recalls collected at baseline and 6 months. Setting: Metropolitan medical complex, Minneapolis, MN, USA. Subjects: Two hundred adults, aged 18–60 years. Results: Cross-sectionally, fast-food consumption was significantly associated with higher daily total energy intake ( β =72·5, P =0·005), empty calories ( β =0·40, P =0·006) and BMI ( β =0·73, P= 0·011), and lower HEI-2010 score ( β =−1·23, P= 0·012), total vegetables ( β =−0·14, P= 0·004), whole grains ( β =−0·39, P= 0·005), fibre ( β =−0·83, P= 0·002), Mg ( β= −6·99, P= 0·019) and K ( β =−57·5, P= 0·016). Over 6 months, change in fast-food consumption was not significantly associated with changes in energy intake or BMI, but was significantly inversely associated with total intake of vegetables ( β =−0·14, P= 0·034). Conclusions: Frequency of fast-food consumption was significantly associated with higher energy intake and poorer diet quality cross-sectionally. Six-month change in fast-food intake was small, and not significantly associated with overall diet quality or BMI.